Effects of Shexiang Baoxin pill combined with exercise rehabilitation training on long-term prognosis of CTO-PCI patients: study protocol for randomized controlled trial - Liu, Ziye; Liang, Shuo; Guo, Xiaoping; Zhao, Yuying (Frontiers in Medicine, 2025)
BackgroundCTO-PCI is generally successful, but 40–55% of patients experience coronary microvascular dysfunction (CMVD) afterward, raising the risk of cardiovascular issues. Shexiang Baoxin Pill (SBP) aids angiogenesis and cardiovascular health, while exercise rehabilitation boosts coronary collateral circulation. However, the combined impact of these treatments on CTO-PCI patients remains under-researched.MethodsThis prospective, single-center, randomized controlled trial involves CTO-PCI patients divided into four groups: Shexiang Baoxin pill, exercise rehabilitation, combined, and control. The exercise protocol includes pre-assessment, a three-phase prescription, CPET-based intensity grading, various exercise methods, remote monitoring, and quality control. The primary outcome is coronary microcirculation assessed by myocardial contrast echocardiography and stress myocardial perfusion imaging 1-year post-surgery. Secondary outcomes include angina incidence, major adverse cardiovascular events (MACE), quality-of-life improvements, and mechanism-related biological indicators, with safety outcomes monitoring liver and kidney function. Data will be analyzed statistically.DiscussionThis study will demonstrate the positive effects of Shexiang Baoxin pill combined with exercise rehabilitation training in improving coronary microcirculatory conditions, reducing major adverse cardiovascular events, and improving quality of life in patients with CTO-PCI. The results of this study will provide new insights into the CTO-PCI patients’ long-term rehabilitation.Clinical trial registrationITMCTR2025000965, Effect of Shexiang Baoxin Pill combined with exercise rehabilitation training on the long-term prognosis of patients with CTO-PCI, Registered on 28 February, 2025.